Pengaruh Pijat Oksitosin Terhadap Lama Persalinan Kala I Fase Aktif Pada Ibu Primigravida Di Praktik Mandiri Bidan Tahun 2023: Indonesia - Pamungkas, Monica Sri; Luthfi, Amir; Dhilon, Dhini Anggraini (Evidence Midwifery Journal, 2024)
Childbirth is a natural process that occurs in every woman, but it can also turn into pathology with prolonged labor. One of the non-pharmacological therapies that is quite effective is oxytocin massage which is considered to be able to trigger labor contractions, provide a feeling of relaxation to the mother in labor, reduce uterine muscle tension, increase uterine contractions and make the process of lowering the fetal head shorter. The aim of this study was to determine the effect of oxytocin massage on the length of labor in primigravida mothers in the first stage of the active phase. The type of research is quantitative research, the research method uses Quasi Experimental with a post test only group design. The sample in this study consisted of 20 mothers giving birth, with each group consisting of 10 respondents using an accidental sampling technique. Data were analyzed using the Mann Whitney test which was previously tested for normality. The results of the univariate analysis showed that 18 respondents (90%) were in the 20-25 year age range, 19 respondents (95%) had a high school/equivalent education and 18 respondents (90%) worked as housewives. It is known that the mean length of labor in the first stage of active phase with Oxytocin Massage is 4.87 hours and without Oxytocin Massage is 6.49 hours. The results of bivariate analysis of the effect of oxytocin massage on the length of labor in primigravida mothers in the first stage of the active phase with a significance value (p value = 0.003). The conclusion is that there is a significant influence between oxytocin massage on the length of labor in primigravida mothers in the first stage of the active phase in the Midwife's Independent Practice in 2023. Suggestions for midwives are expected to be able to help mothers give birth by meeting the mother's need for comfort, providing childbirth care by applying oxytocin massage techniques so that labor can take place effectively and safely both in terms of the length of labor and the condition of the baby being born.